2020
DOI: 10.1177/2164956120964716
|View full text |Cite
|
Sign up to set email alerts
|

Group Acupuncture Therapy With Yoga Therapy for Chronic Neck, Low Back, and Osteoarthritis Pain in Safety Net Setting for an Underserved Population: Design and Rationale for a Feasibility Pilot

Abstract: Chronic pain is prevalent in the United States, with impact on physical and psychological functioning as well as lost work productivity. Minority and lower socioeconomic populations have increased prevalence of chronic pain with less access to pain care, poorer outcomes, and higher risk of fatal opioid overdose. Acupuncture therapy is effective in treating chronic pain conditions including chronic low back pain, neck pain, shoulder pain, and knee pain from osteoarthritis. Acupuncture therapy, including group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 79 publications
(116 reference statements)
0
11
0
Order By: Relevance
“…A detailed plan for our study is described in a previous publication. 41 We used a repeated measures quasi-experimental design in which measurements were taken on participants before (when receiving usual care) and at intervals after treatment was initiated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed plan for our study is described in a previous publication. 41 We used a repeated measures quasi-experimental design in which measurements were taken on participants before (when receiving usual care) and at intervals after treatment was initiated.…”
Section: Resultsmentioning
confidence: 99%
“…GA sessions were staffed with one acupuncturist who could initiate treatment of up to four participants per hour. 41 The acupuncture therapy intervention, outlined in the manual, 44 consisted of acupuncture needling and a range of other East Asian medicine modalities including Gua Sha, Tui Na, and auricular therapy with needles and/or ear seeds. Acupuncture sessions lasted from 15 to 40 min, with the timing often adapted to facilitate participants starting their YT session.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In liver transplant patients, it may be beneficial to use low-cost complementary therapies in order to ensure the participation of the individual in their own care and to reduce the symptoms of the disease (Kugler et al, 2009). Studies conducted in Turkey and other countries have shown that people with chronic diseases usually use modern treatment methods alone or in combination with other integrative therapies (Demir & Saritas, 2020; Edwards et al, 2018; Ketai et al, 2021; Nielsen et al, 2020; Rottman et al, 2020). Progressive relaxation exercises, one of these integrative treatment methods, are a type of exercise that involves stretching and relaxation of a large muscle group from hands to feet (Cengiz & Komurkara, 2020).…”
Section: Introductionmentioning
confidence: 99%